Design, validation, and application of a 1K liquid chip for genome-wide association analysis in Alpine Merino sheep - Guo, Tingting; Yuan, Chao; Liu, Jianbin; Yang, Bohui (Frontiers in Veterinary Science, 2025)
Because wool is an important animal fiber and mutton is rich in nutrients, fine wool sheep are one of the most economically important livestock. China has been selecting and breeding high-quality fine wool sheep breeds since the 1950s and is the largest processing and consuming country for fine wool sheep. In this study, blood samples were collected from Alpine Merino sheep (AMS), Chinese Merino sheep (CMS), Aohan fine wool sheep (AHS), and Qinghai fine wool sheep (QHS). Genomic DNA was extracted and subjected to genome resequencing. GenoBait technology was used for probe design and site optimization, followed by synthesis of a low-density liquid-phase chip. Finally, 409 AMS were randomly selected to verify the chip. The results showed that a total of 1,012 single-nucleotide polymorphism sites (SNPs) were screened and retained for the synthesis of a low-density liquid chip for genome-wide selection and population genetics structure analysis. This chip can provide a useful tool for genome analysis of fine wool sheep and lay a solid foundation for subsequent breeding work.